(untitled) (Bangladesh Journal of Anatomy, 2011)
Context: Aiming the effects of severity of diabetes mellitus on human placenta and the neonatal outcome, a quantitative study at the macroscopic level was designed. Material and Methods: Sixty post caesarean section human placentae were studied of which thirty were from mothers having established diabetes mellitus considered as EDM and thirty were from control mother having no diabetes mellitus. EDM mothers were treated with insulin. Venous plasma glucose level (fasting and 2 hours after breakfast) of the EDM mothers in 2nd and 3rd trimester were recorded and the mean of the values were calculated. Results: The values ranged from 5.93 to 10.10mmol/L and the mean was 7.28±0.99 m mol/L. The mothers having EDM were grouped according to the mean venous plasma glucose level. The mothers having a mean level up to 8.3 m mol/L and those having a level above 8.3 m mol/L were designated as the Low-EDM and High- EDM group respectively. Placental weight in Control, Low-EDM and High-EDM groups were 414.93±95.41, 403.83±68.53 gm and 446.33± 82.23gm respectively. The value showed lower mean value in Low-EDM group. The difference did not reach a significant level. The neonatal weight in Control, Low-EDM and High-EDM groups were 2958.33±537gm, 2997.91±540 gm and 3300.00±379 gm respectively. The weight of the neonates did show a tendency towards being heavier in EDM groups but did not reach the significant level. There was a significant positive correlation between the neonatal weight and placental weight in control and Low-EDM group. Key words: Established diabetes mellitus; Placenta; Neonates DOI: http://dx.doi.org/ 10.3329/bja.v9i1.8150 Bangladesh Journal of Anatomy January 2011, Vol. 9 No. 1 pp 53-58